2007
DOI: 10.1002/ijc.22899
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talks between cyclooxygenase‐2 and tumor suppressor protein p53: Balancing life and death during inflammatory stress and carcinogenesis

Abstract: Overexpression of Cyclooxygenase-2 (COX-2) is observed in most tumor types. Increased COX-2 activity and synthesis of prostaglandins stimulates proliferation, angiogenesis, invasiveness and inhibits apoptosis. Many stress and proinflammatory signals induce COX-2 expression, including oxyradicals or DNA-damaging agents. The latter also induces p53, a transcription factor often inactivated by mutation in cancer. Several studies have identified complex cross-talks between p53 and COX-2, whereby p53 can either up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 78 publications
5
68
0
Order By: Relevance
“…Many findings have contributed to establishing the relationship between the expression of apoptosis and COX-2 (Benoit et al 2006;de Moraes et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many findings have contributed to establishing the relationship between the expression of apoptosis and COX-2 (Benoit et al 2006;de Moraes et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways are involved in the expression of p53, a tumor-suppressor gene (Hsu et al 2007). Several studies have found that stimulation of COX-2 also induces p53, which accelerates after post-translation modification in response to DNA damage (de Moraes et al 2007) and an increase of p53 results in antiproliferative effects, including cell cycle arrest, DNA repair, or apoptosis (Sengupta and Harris 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this report, our data reveal that 15d-PGJ 2 treatment results in the p53 protein accumulation in human breast cancer (MCF-7) cells. Several studies have identified complex crosstalks between p53 and COX-2, whereby p53 can either up-or downregulate COX-2, which in turn controls p53 transcriptional activity (de Moraes et al, 2007). However, the molecular basis of such p53-COX-2 axis is open to debate.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms were postulated to contribute to the anti-apoptotic effect of Cox-2 including the metabolism of its pro-apoptotic substrate arachidonic acid and subsequent synthesis of the survival factor prostaglandin, as well as augmenting expression and activity of Bcl-2 and Akt (Figure 4). 148 In addition, Cox-2 appears to directly modulate p53 activity at several levels as firstly, overexpression of Cox-2 was found to promote the binding of p53 to MDM2 resulting in a diminished nuclear accumulation of p53 protein. Consistent with this, Cox-2 inhibitors enhanced chemosensitivity by downregulating HDM2 thereby augmenting p53 stability.…”
Section: P53 and Mitogen-activated Protein Kinasesmentioning
confidence: 99%
“…44,147 Cox-2, a crucial enzyme in prostaglandin synthesis is often overexpressed in many solid tumors and associated with tumor aggressiveness due to its well documented anti-apoptotic and tumor-promoting capabilities. 148,149 Cox-2 was also demonstrated to regulate p53-induced apoptosis, as the rate of cell death following DNA damage was potentiated not only in Cox-2-deficient cells, but also in cells in which Cox-2 activity was suppressed by non-steroidal anti-inflammatory drugs such as NS-398 and celecoxib. Several mechanisms were postulated to contribute to the anti-apoptotic effect of Cox-2 including the metabolism of its pro-apoptotic substrate arachidonic acid and subsequent synthesis of the survival factor prostaglandin, as well as augmenting expression and activity of Bcl-2 and Akt (Figure 4).…”
Section: P53 and Mitogen-activated Protein Kinasesmentioning
confidence: 99%